Peer-to-peer computing applications, architecture, protocols, and challenges - Kwok, Yu-Kwong Ricky (Boca Raton, FL Taylor & Francis, 2012)
Preface Peer-to-peer computing, at least on a conceptual level, is a genuine paradigm shift--intelligence is at the edge, computing is completely decentralized, and the network is just there to knit the distributed intelligence together. Indeed, with advancements in hardware technology, proliferation of the open source development culture, and abundant information at our fingertips, computing power and user competence at the edge of the network has risen to an unprecedented level. Thus, devices at the edge (not restricted to desktop PCs) can congregate and share their resources (computing power, file data, etc.) to provide services to participating users in a self-sufficient manner, without the need of dedicated servers. With potentially up to millions of machines participating simultaneously (e.g., when some hot events are occurring), the aggregated computing resources can dwarf any powerful server farm. Well, well, well, ...these are "conceptual level" thinking as of now. There are still many road-blocks to such a vision, even though we do see millions of machines working together in a P2P manner (e.g., streaming live video events). Again, as the old saying goes, the devils are in the details. Thinking of such gigantic scale of sharing computing resources is one thing, while implementing the idea is definitely another. Road-blocks to the grand vision of truly global P2P sharing include architectural maintenance problems arising from the sheer scale of the system, incentives for truthful cooperation, trust among peers when they need to accept data from remote sources, security issues caused by the inevitable existence of malicious users, etc.
Keywords: Peer-to-peer architecture (Computer networks)